Kondisi Emosi Pada Tokoh Lengkara Dalam Novel 00.00 Karya Anugerah Ameylia Falensia - Yeni Ariyaniningsih; Eva Dwi Kurniawan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The research aims to find out what the emotional state of teenagers in novels is by using the theory of literary psychology according to David krech's book of emotional classification. It identifies the underlying emotions, the emotions associated with sensory stimulation, emotions related to self-assessment and emotions connected with others. This research method employs qualitative methods using descriptions, dialogues and characters that relate to the emotional reactions of characters. The results of analysis show that the novel's emotional main character has such basic emotions as happiness, anger, fear and sadness in various situations. This study provides insight into how the emotional condition of the novel can be perceived by the theory of David krech. This study may be a reference to further research on emotional states in literature.